ショウワ キチ ノ コウソウ キショウ ト キセツ ジュンカンガタ ノ キジュツ - 清野, 善兵衛; セイノ, ゼンベイ; 鈴木, 信雄; スズキ, ノブオ; SEINO, Zenbei; SUZUKI, Nobuo (国立極地研究所, 1964)
P(論文) Seasonal mean values of heights and temperatures at the selected pressure surfaces are computed, using the aerological data obtained during the 4 th (1960) and the 5 th (1961) wintering observations at the Syowa Base, Antarctica. Main characteristics of the seasonal and yearly variations both in the antarctic troposphere and the stratosphere are investigated by means of these limited data. Four vertical time sections (from the surface to 30mb) of Feb. May. Aug. Oct. -Nov., representing each season respectively, are made based on these data, and some notable features of seasonal circulation patterns in 1961 over the Syowa Base are briefly described. In addition, in supplementing this single station data analysis, IAAC's synoptic weather charts in microfilm are used to locate relative pressure systems, and at the same time, for rough estimation of circulation intensity, meridional temperature gradients between the Syowa Base and Marion Island in the middle latitude, together with difference in their annual variations, are utilized. Characteristics of the seasonal circulations in 1961 are summarized as follows : Summer : In the troposphere, weak anticyclonic systems predominate over the east continent and weak circulations of E-ly with slightly N and S components are seen. However, in the location and movement of these systems, W-ly wind circulation is also seen. Cyclonic activities are such that most of lows move on toward the east within the low pressure belt off the base, and, except at the surface, N or NE-ly winds by these systems are very weak in the upper layer, so there was little influence to the air over the base. For the layer from the lower to middle stratosphere, weak W-ly wind generally prevails but variation of the wind direction is also seen upon appearance of anabatic and katabatic fields. In the upper stratosphere, weak E-ly wind with N component can be seen. Autumn : For the layer from the middle troposphere to the lower stratosphere, S or SW-ly strong jets come to be observed due to the ...